Creating an Interinstitutional Agricultural Systems Management Distance Education Program - Slocombe, John W.; Ebert, Kerri; Schumacher, Leon G. (Journal of Agricultural Systems, Technology, and Management, 2012)
Four Midwestern universities collaborated to develop a distance education delivery network for agricultural systems management courses. These undergraduate courses were initially offered to students at Iowa State University, Kansas State University, University of Missouri, and University of Nebraska-Lincoln with funding from a USDA Higher Education Challenge Grant and affiliated with the Great Plains Interactive Distance Education Alliance. The program has expanded and is now available nationally. This paper describes how the project was developed, the interinstitutional collaboration process, and the procedures and infrastructure created to achieve learning and delivery objectives.